ANALISIS DISTRIBUSI DAN KETIMPANGAN PENDAPATAN BURUH PANEN KELAPA SAWIT RAKYAT DI KECAMATAN AIR RAMI KABUPATEN MUKOMUKO PROVINSI BENGKULU - Nola Windirah; Agung Trisusilo; Nyayu Neti Arianti; Reswita (JURNAL AGRICA, 2026)
The Indonesian palm oil industry faces various environmental challenges, prompting the government to establish the Indonesian Sustainable Palm Oil (ISPO) standard as an instrument for sustainable business governance and greenhouse gas emission mitigation. However, ISPO implementation still faces obstacles, particularly in smallholder plantations, which account for 40.5% of the total national palm oil plantation area. Upstream workers, particularly harvest workers, play a strategic role in the sustainability of this industry. Air Rami District, Mukomuko Regency, Bengkulu Province, is one of the palm oil production centers with 13,325 hectares of smallholder plantation status in 2023. This study aims to analyze the distribution and income inequality of smallholder palm oil harvest workers in Mukomuko Regency, Bengkulu Province. The method used is quantitative descriptive analysis with income calculations and the Gini coefficient. The results show that the distribution of harvest worker income consists of 76.7% coming from the agricultural sector (harvest laborers, plantations, fisheries, and livestock) and 23.3% coming from non-agricultural sectors (entrepreneurship and others). Meanwhile, income distribution as harvest laborers accounts for 55.3% of total income. Furthermore, income inequality among smallholder oil palm harvest laborers is moderate, with a Gini coefficient of 0.47. Furthermore, income inequality decreases with income diversification, with a Gini coefficient of 0.40.